Analysis of unimorph piezoceramic patches on damped square shaped plate - Mohd Najib , Ali Mokhtar; Fairul Azni, Jafar; Ahmad Yusairi, Bani Hashim; Hazman, Hasib; Mohd Nazrin, Muhammad (Trans Tech Publications, Switzerland, 2013)
Active damping using piezoelectric element is one of the effective techniques to counter vibration problems. A 3D finite-element model is developed as part of investigation for damping control. The piezoelectric patches are surface bonded on quadrilateral thin plate and supported with spring damper elements. The main goal of this paper is to investigate mechanical characteristics of piezoceramic array on membrane and the effect of force excitation using small motor and electric excitation on the system. The system setup produced small vibration displacement and does not displace the plate beyond elastic strain region. The results show the linear behavior of piezoceramic and the correlation between electric excitation, motor vibration and displacement at the centre of the plate at different frequency range. The mode shapes and natural frequencies at low frequency spectrum are also presented. Therefore, the results can be used as reference to develop damping system with aid of piezoelectric patches.